THE ANALYSIS OF THE STRESS-STRAIN STATE OF THE SYSTEM «BASEMENT - PILE FOUNDATION – STRUCTURE» CONSIDERING SWELLING PROPERTIES OF SOILS (Academic journal Industrial Machine Building Civil Engineering, 2017)
This work analyzes factors affecting swelling soils and presents a calculation algorithm of structure on swelling soils base for the plane problem. In this work an analysis of the factors influencing the swelling of soils is made, the algorithm for calculating the structure with the base with swellable soils for a plane problem is given. At the same time, the swelling process is considered as an additional influence, close in nature to temperature, and the swelling soil is considered a material having orthotropic properties. The value of the relative swelling depends on the level of the stress state, while the value of the main stresses is compared with the magnitude of the pressure of swelling. Therefore, to determine the deformation characteristics of the swelling soil, several variants of the stressed state of the soil have to be considered. The effectiveness of the obtained solution has been verified according to the example for pile foundations.
Keywords: swelling soils; shrinkage of swelling soils; orthotropic properties; final element method; system «basement – pile foundation – structure»